APPLICATION OF ONLINE-BASED LEARNING MODELS IN THE PANDEMIC Period (COVID-19) IN DEVELOPING LEARNING INDEPENDENCE FOR STUDENTS AT UNIVERSITY LEVELS - Harmelia Harmelia (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study analyzed the application of online-based learning models during the pandemic (Covid-19) in helping develop independent learning for university level students.This research uses descriptive qualitative research methods. The population in this study were students of FEB UPI YPTK Padang and for the number of samples calculated using the Slovin formula, 350 samples were obtained. The sampling technique was purposive random sampling. Retrieval of data in this study is by distributing questionnaires to students using google forms. The effectiveness of online learning ((X1) is .298 or 29.8%. While the calculation for the Respondents' Achievement Rate (TCR), it is found that 50% more give an assessment indicating that they strongly approve of online learning or distance learning (PJJ) during the pandemic period. for the variable online learning constraint ((X2) is .488 or 48.8%. While the calculation for Respondent Access Level (TCR) is obtained that 45% more give a higher assessment of the constraints they face from online learning or distance learning ( PJJ) this.For the independent learning variable (Y) the results of the F test processing obtained F count of 122,832 with a significance value of 0,000. Meanwhile, the results of the Respondents' Achievement Level (TCR) showed that there was a significant increase in fostering learning independence for students, it was seen that 65% of students stated that they were more active in completing class assignments and looking for recovery materials